Israel in Foreign Policy of the United Arab Emirates: from Confrontation to Normalization - E. S. Melkumyan (Vestnik MGIMO-Universiteta)
The article analyzes the transformation of the UAE policy towards Israel. Special at- tention is paid to the development of the country’s foreign policy priorities amid consolida- tion of the federal state. Strengthening relations with the Arab states during the first decades of the UAE history, participation in the Arab League, which consolidated the states of the Arab world, support of its opposition to Israel were the factors determining the anti-Israeli policy of the Emirates. The official position of the UAE was formulated under the influence of pan-Arab rhetoric and in no way differed from the position reflected in the documents of the Arab League summits. The peace process around the Arab-Israeli conflict launched since the 1991 in the framework of the Madrid Peace Conference did not result in the establish- ment of contacts between the UAE and Israel. The adjustment of Emirates’ foreign policy began after the aggravation in the Middle East, when countries such as Syria, Yemen and Libya were engulfed in conflicts. During this period, the Arab-Israeli conflict gradually lost its central role for the Arab world; the states of the Persian Gulf began to establish contacts with Israel, united by common fears about the strengthening Iran. The article discussed the path of stabilization between the United Arab Emirates and Israel including the role of their informal ties. The normalization between the UAE and Israel, outlined in August 2020 with the active participation of the United States, gave impetus to the establishment of relations between the two countries in various areas of mutual interest. The article traces the connec- tion between the specific areas of cooperation with Israel and those which were set byа Abu Dhabi as the key priorities of its national strategic development.